The Contribution of Ibn Jinni's Thoughts in the Science of al-Lughah (Linguistics) - Ramadhani, Nabila; Ahmad, Hafizah; Salsabila, Nawa Husna; Faruqy, Muhammad Ma'ruf (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Ilmu al-Lughah is one of the branches of science that studies Arabic and has a very important position. In Arabic itself, this study has experienced many developmenhts. In the process of its development, this study produced many branches of science and of course this gave birth to many important figures who participated in channeling their thoughts in the study of Science al-Lughah, including Ibn Jinni. This article looks at Ibn's thoughts in the study of Science al-Lughah. This study aims to explain and describe the contribution of Ibn Jinni in Science al-Lughah. Collecting research data using literature related to the discussion and collecting data obtained from various sources, then the data is analyzed and described.